Long-term active layer monitoring at CALM sites in the Russian European North. (3rd July 2021) - Kaverin, Dmitry; Malkova, Galina; Zamolodchikov, Dmitry; Shiklomanov, Nikolay; Pastukhov, Alexander; Novakovskiy, Alexander; Sadurtdinov, Marat; Skvortsov, Andry; Tsarev, Andry; Pochikalov, Alexander; Malitsky, Sergei; Kraev, Gleb
ABSTRACT: This paper presents results from long-term active layer monitoring at four CALM sites in the Russian European North. Observational records range from 10 to 24 years in length (1996–2019). The impact of climatic and landscape parameters on active layer thickness has been assessed through linear regression. The temporal dynamics of climatic parameters, responsible for the thaw depth changes, were investigated. The long-term data indicate that the active-layer thickness has increased at all the monitoring sites, in response to changes in both summer and winter climatic parameters. The surface organic layer also serves as a major landscape factor influencing spatial patterns of thaw depth and climate-induced rates of permafrost thawing.